2015
DOI: 10.1002/sce.21185
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Short‐ and Long‐Term Learning Effects Between Stereoscopic and Two‐Dimensional Film at a Planetarium

Abstract: Science centers such as museums and planetariums have used stereoscopic ("three-dimensional") films to draw interest from and educate their visitors for decades. Despite the fact that most adults who are finished with their formal education get their science knowledge from such free-choice learning settings very little is known about the effect of stereoscopic film presentation on their science learning. We explored this issue by designing a quasi-experimental field trial with a short film about the shape of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 74 publications
3
9
0
Order By: Relevance
“…This study is aligned with the studies that found no overall difference in the effectiveness of the two viewing formats (Cid & Lopez, 2010;Price, Lee, & Malatesta, 2014;Price et al, 2015;Wuerzburger, 2017). Meanwhile, those studies differed from this one.…”
Section: Discussion and Recommendationssupporting
confidence: 84%
“…This study is aligned with the studies that found no overall difference in the effectiveness of the two viewing formats (Cid & Lopez, 2010;Price, Lee, & Malatesta, 2014;Price et al, 2015;Wuerzburger, 2017). Meanwhile, those studies differed from this one.…”
Section: Discussion and Recommendationssupporting
confidence: 84%
“…This is one example that shows that linking Earth‐based observations with sophisticated models of a space‐based perspective supports understanding. Similar results were obtained by Price, Lee, Subbarao, Kasal, and Aguilera () in a study where a three‐dimensional film, in their case about galaxy‐related concepts, was shown to adults.…”
Section: Previous Researchsupporting
confidence: 85%
“…research (AER) community to further investigate the connection between success in learning astronomy and extrapolating three dimensionality [76,78,90,[93][94][95]. Here, virtual and augmented reality, and planetaria, are found to offer new possibilities for approaching this [96][97][98][99][100][101][102][103]. However, such resources must be used with considerations; Tversky et al [104] say, "Like all good things, animation must be used with care" (p. 258).…”
Section: The Multidimensionality Hierarchy and Extrapolating Threementioning
confidence: 99%